Nationalismus als Umkehr: Etwas zur jüdischen Meta-Politik der Moderne - Biemann, Asher D. (Naharaim, 2022)
"Metapolitics" is an ambiguous term. Recent philosophers have claimed the concept for neo-conservative, even right-wing agendas, while others have employed it to signal radical discontent with politics altogether. Beginning with Peter Viereck's characterization of Nazi ideology as "Meta-Politics," this essay works its way back from an "irrational," "volkish," and supposedly "conservative" concept to another use of "Metapolitics" as found in Martin Buber and Hermann Cohen that was rooted in a liberal tradition of the Enlightenment - especially in August Schlözer and Saul Ascher. Both, Buber and Cohen, linked "metapolitical politics" to prophetic and theopolitical sensibilities. As such, the prophetic motif of turning (Teshuvah) loomed large at the center of their respective philosophies of nationalism. But it was a theme that also connected a wide range of thinkers, including Hans Kohn and Leo Baeck, and which emerged as a Leitmotiv of cultural and spiritual Zionism as well as of the modern Renaissance of Jewish culture. Drawing on Moritz Lazarus, the essay argues that the recurring trope of turning helped establish a paradoxical nationalism founded not upon self-empowerment and political othering but on self-criticism. Concluding with a brief excursion on Abraham Joshua Heschel's prophetic politics in the Civil Rights Movement, the essay gestures towards the possibility of nationalism as collective introspection and self-reformation.